3-Dimensional ZnO/CdS nanocomposite with high mobility as an efficient electron transport layer for inverted polymer solar cells. Issue 17 (14th April 2016) - Wang, Yilin; Fu, Haiyan; Wang, Ying; Tan, Licheng; Chen, Lie; Chen, Yiwang
Abstract : A 3-dimensional ZnO/CdS nanocomposite with high mobility as an electron transport layer boosts device efficiency to 8.0% for inverted polymer solar cells. Abstract : The inclusions of solution-processed ZnO electron transport layers (ETLs) of inverted polymer solar cells can lead to various surface defects, which can act as interfacial recombination centers for photogenerated charges and thereby can lead to degradation of the device performance. Three-dimensional (3D) CdS with different morphologies, such as flower-like CdS (F-CdS), branched CdS (B-CdS), and spherical CdS (S-CdS), are synthesized to modify ZnO ETLs, by effectively removing the intragap states of the ZnO nanocrystal films by forming ZnO/F-CdS, ZnO/B-CdS, and ZnO/S-CdS composite ETLs, respectively. Moreover, ZnO/CdS possesses higher electron mobility and provides a larger interface between the ETL and active layer, which is beneficial for enhancing the power conversion efficiency (PCE) of the inverted organic solar cells. In particular, a device based on a ZnO/S-CdS ETL and thieno[3, 4- b ]-thiophene/benzodithiophene (PTB7):[6, 6]-phenyl-C71-butyric acid methyl ester (PC71 BM) active layer achieved a PCE of 8.0%, together with better long-term stability.